Choose MyPlate: Drink Water Instead of Sugary Drinks - Jeanine Beatty; Karla Shelnutt; Gail Kauwell (EDIS)
The regular consumption of sugary drinks has greatly increased over the past few decades. Most adults consume about 400 calories per day as beverages, and regular soda is the number one drink. The added sugars and calories in sugary drinks can really add up — so rethink what you drink! Use one or more of the tips provided to drink more water and get on the right track to living a healthier life. This 3-page fact sheet was written by Jeanine Beatty, Karla Shelnutt, and Gail Kauwell, and published by the UF Department of Family Youth and Community Sciences, April 2013.